Neural networks underlying affective states in a multimodal virtual environment: contributions to boredom - Mathiak, Krystyna A.; Klasen, Martin; Zvyagintsev, Mikhail; Weber, Rene; Mathiak, Klaus (Frontiers in Human Neuroscience, 2013)
The interaction of low perceptual stimulation or goal-directed behavior with a negative subjective evaluation may lead to boredom. This contribution to boredom may shed light on its neural correlates, which are poorly characterized so far. A video game served as simulation of free interactive behavior without interruption of the game’s narrative. Thirteen male German volunteers played a first-person shooter game (Tactical Ops: Assault on Terror) during functional magnetic resonance imaging (fMRI). Two independent coders performed the time-based analysis of the audio-visual game content. Boredom was operationalized as interaction of prolonged absence of goal-directed behavior with lowered affect in the Positive and Negative Affect Schedule (PANAS). A decrease of positive affect correlated with response amplitudes in bilateral insular clusters extending into the amygdala to prolonged inactive phases in a game play and an increase in negative affect was associated with higher responses in bilateral ventromedial prefrontal cortex. Precuneus and hippocampus responses were negatively correlated with changes in negative affect. We describe for the first time neural contributions to boredom, using a video game as complex virtual environment. Further our study confirmed that positive and negative affect are separable constructs, reflected by distinct neural patterns. Positive affect may be associated with afferent limbic activity whereas negative affect with affective control.